2016
DOI: 10.21548/32-2-1380
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acids, Phenolic Aldehydes and Furanic Derivatives in Oak Chips: American vs. French Oaks

Abstract: Phenolic acids (gallic, vanillic, syringic and ellagic acids), phenolic aldehydes (vanillin, syringaldehyde, coniferaldehyde and sinapaldehyde) and furanic derivatives (furfural, 5-methylfurfural and 5-hydroxymethylfurfural) were quantified in commercial American and French oak chips. Chips with different sizes and toast degrees were used. Compounds were extracted directly from the wood samples in order to determine possible differences among woods as well as toast degree. Likewise, the compounds were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…The concentration of ellagic acid was significantly higher in Q. sessiliflora (French and Romanian) green wood than in Q. alba and Q. humboldtii oaks (560.73, 556.16, 352.72 and 286.88 μg/g of wood, respectively). These results are similar to those observed by different authors in green wood (Cadahía and Fernández de Simón, 2004) or in dried or toasted wood (Prida and Puech, 2006;Cabrita et al, 2011) from Q. sessiliflora and Q. alba oaks. In addition, ellagic acid content was similar in Q. humboldtii and Q. alba green wood.…”
Section: Low Molecular Weight Phenolic Compounds (Lmwp)supporting
confidence: 92%
See 1 more Smart Citation
“…The concentration of ellagic acid was significantly higher in Q. sessiliflora (French and Romanian) green wood than in Q. alba and Q. humboldtii oaks (560.73, 556.16, 352.72 and 286.88 μg/g of wood, respectively). These results are similar to those observed by different authors in green wood (Cadahía and Fernández de Simón, 2004) or in dried or toasted wood (Prida and Puech, 2006;Cabrita et al, 2011) from Q. sessiliflora and Q. alba oaks. In addition, ellagic acid content was similar in Q. humboldtii and Q. alba green wood.…”
Section: Low Molecular Weight Phenolic Compounds (Lmwp)supporting
confidence: 92%
“…Very few oaks fully meet these conditions, and those most used belong to the white oak group. In the last few years, other white oaks have been studied for use in oenology with the aim of comparing their characteristics with those of traditional oaks (Q. robur, Q. sessiliflora and Q. alba), as is the case of Q. pyrenaica and Q. faginea (Canas et al, 2000;Cadahía et al, 2001a,b;Fernández de Simón et al, 2006;Jordão et al, 2007;Gonçalves and Jordão, 2009;Cabrita et al, 2011;Gallego et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Ever since OIV approved the use of wood alternatives for barrels, different methods are applied to shorten the ageing period of alcoholic beverages and enhance their phenolic and flavour profile [82]. Recently, more attention is given to the use of wooden fragments and powders for the rapid inducing ageing character of brandies [37,46,[83][84][85], with reducing the lasting period between days to some weeks.…”
Section: Aged Distillates Biomarkersmentioning
confidence: 99%
“…In the literature, there are some studies on aroma compounds in wines aged using alternatives techniques [6,7]. Cabrita et al [8] investigated the furanic derivatives, phenolic acids, and phenolic aldehydes present in oak wood chips, comparing American oak and French oak. Their results indicated that the wine aged with French oak wood chips is richer in aroma compounds than the wine aged with American oak chips.…”
Section: Introductionmentioning
confidence: 99%